2013
DOI: 10.4161/cib.22321
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient transfer to plants by phylogenetically diverse fungi suggests convergent evolutionary strategies in rhizospheric symbionts

Abstract: Most land plants are able to form symbiotic associations with fungi, and in many cases these associations are necessary for plant and fungal survival. These plant/fungal associations are formed with mycorrhizal (arbuscular mycorrhizal or ectomycorrhizal) or endophytic fungi, fungi from distinct phylogenetic lineages. While it has been shown that mycorrhizal fungi are able to transfer nutrients to plant roots in exchange for carbon, endophytes have been thought as asymptomatic colonizers. Recently, however, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…These two lifestyles are linked through reciprocal nutrient exchange with a host plant, whereby the fungus receives carbon in exchange for insect-derived nitrogen. Interestingly, Metarhizium is phylogenetically related to other endophytes26 and we suggest that their evolution as insect pathogens, as well as their ability to translocate nitrogen27, allowed them to effectively barter a specialized nitrogen source (that is, insects) with host plants for photosynthate. While there has been previous work that has indicated the role that root colonizing fungi play in plant nutrient acquisition, the present study provides information on multi-role lifestyles of insect-pathogenic fungi in soil environments.…”
Section: Discussionmentioning
confidence: 89%
“…These two lifestyles are linked through reciprocal nutrient exchange with a host plant, whereby the fungus receives carbon in exchange for insect-derived nitrogen. Interestingly, Metarhizium is phylogenetically related to other endophytes26 and we suggest that their evolution as insect pathogens, as well as their ability to translocate nitrogen27, allowed them to effectively barter a specialized nitrogen source (that is, insects) with host plants for photosynthate. While there has been previous work that has indicated the role that root colonizing fungi play in plant nutrient acquisition, the present study provides information on multi-role lifestyles of insect-pathogenic fungi in soil environments.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that insect pathogenic fungi and EMF can transport insect-derived organic nitrogen into the plant roots ( Klironomos and Hart, 2001 ; Behie et al, 2012 , 2013 ). More broadly, some rhizobacterial symbionts of plants also secrete proteases and degrade denatured proteins and scavenge organic nitrogen from soil ( White et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intimacy of this association was potentially driven by fungal acquisition of plant-fixed carbon. Plants can fix carbon dioxide and are a carbon reservoir, a valuable commodity to fungi [ 77 ]. Plants would allow carbon exchange to a partner that could provide nutrients.…”
Section: Evolutionary Implication Of Nitrogen Transfer By Fungal Smentioning
confidence: 99%
“…The traditional paradigm concerning the population structure of insect pathogenic fungi has focused on the insect host as the driving force. However, the fact that some pathogenic fungi are endophytes ( Beauveria and Metarhizium ) suggests that plant host symbiosis may be a major evolutionary influence [ 77 ]. Insect pathogenic fungi that are incapable of forming plant associations would be more likely to evolve insect host specificity and, in this case, fungal evolution would be driven most influentially by the range of insect hosts.…”
Section: Evolutionary Implication Of Nitrogen Transfer By Fungal Smentioning
confidence: 99%